HFE Gene Mutations as Predisposing Factors for Childhood Acute Lymphoblastic Leukaemia in Iraqi Patients - Ibrahim, Thanaa Kalil; Albandar, Intisar; Jabbar, Shilan; Khalid, Raghda (University of Thi-Qar Journal of Science, 2024)
Hemochromatosis is a prevalent hereditary disorder that causes excess iron to build up in the body to dangerous levels. Hereditary hemochromatosis, also known as HFE-related hemochromatosis is carried on by changes in the HFE gene. Investigating the gene mutations of the HFE gene is a way to explore the prevalence of this disease. This study aims to determine the association between hemochromatosis HFE gene mutations (C282Y and H63D) and childhood acute lymphoblastic leukaemia in patients at Basra Specialized Hospital for Children and AL-sadder Teaching Hospital in the Basra governance. QIAamp DNA and Blood Mini Kit were used to isolate and identify Human genomic DNA and detect mutations in the HFE gene using the DNA hybridization method. In this study, the absence of the C282Y mutations in both patients and the control group was identified. However, testing DNA-based hybridization experiments revealed low detection levels of the H63D (homozygous, heterozygous) mutations; in only 12.5% of patients. The H63D (only homozygous) mutations were present in 10% of the control group. The association between patients and the control group is considered statistically significant. The HFE gene mutations (C282Y and H63D), originate in acute lymphoblastic leukaemia in childhood, thus, this study recommends complementary investigations to illustrate this case in more detail with more cases of patients and discover the hidden agents underlying these mutations.